Genome-wide characterization of SPL family in Medicago truncatula reveals the novel roles of miR156/SPL module in spiky pod development - Wang, Hongfeng (BMC Genomics, 2019)
BACKGROUND: SQUAMOSA Promoter Binding Protein-Likes (SPLs) proteins are plant-specific transcription factors that play many crucial roles in plant growth and development. However, there is little information about SPL family in the model legume Medicago truncatula. RESULTS: In this study, a total of 23 MtSPL genes were identified in M. truncatula genome, in which 17 of the MtSPLs contained the putative MtmiR156 binding site at the coding or 3′ UTR regions. Tissue-specific expression pattern analysis showed that most MtmiR156-targeted MtSPLs were highly expressed in seed and pod. The observation of MtmiR156B-overexpressing plants reveals that MtmiR156/MtSPL modules are not only involved in the development of leaves and branches, but also in the seed pod development, especially the formation of spine on pod. CONCLUSION: The spines on pods are developed in many plant species, which allow pods to adhere to the animals, and then be transported on the outside. This study sheds light on the new function of SPL family in seed dispersal by controlling the formation of spiky pod, and provides insights on understanding evolutionary divergence of the members of SPL gene family among plant species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5937-1) contains supplementary material, which is available to authorized users.